Pengaruh Kompensasi Finansial, Disiplin Kerja Burn Out terhadap Kinerja pada Pegawai Rumah Sakit Umum Daerah Kilisuci Kota Kediri - Frida Ariana Sukmanata; Eko Widodo; Indah Yuni Astuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of financial compensation, work discipline, and burnout on employee performance at the Kilisuci Regional General Hospital in Kediri City. The research method used is a quantitative method with a descriptive approach. Data collection in this study was conducted by distributing questionnaires to employees of the Kilisuci Regional General Hospital in Kediri City and analyzed using the SPSS Version 25 application. The data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-Test, F Test, and R2 Coefficient of Determination Test. In the Validity Test, it was found that all question items (X1, X2, X3, and Y) had a significance value of 0.000 < 0.05, indicating that each variable was declared valid. Then in the Reliability Test, each variable was declared reliable because it had a Cronbach's Alpha value of > 0.60. Then in the t-Test, it was found that the financial compensation variable. and burn out simultaneously on employee performance at the Kilisuci Regional General Hospital, Kediri City.